Placement of an elastic, biohybrid patch in a model of right heart failure with pulmonary artery banding - Hayashi, Yasunari; Kim, Seungil; Fujii, Taro; Pedersen, Drake Dalton; Ozeki, Takahiro; Jiang, Hongbin; D’Amore, Antonio; Wagner, William R. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionIn a model of right heart failure secondary to pulmonary artery banding (PAB), a mechanical approach using an elastic, biodegradable epicardial patch with integrated extracellular matrix digest was evaluated for its potential to inhibit disease progression.MethodsAdult male syngeneic Lewis rats aged 6–7 weeks old were used. Biohybrid cardiac patches were generated by co-processing biodegradable poly(ester carbonate urethane) urea (PECUU) and a digest of the porcine cardiac extracellular matrix. Three weeks after PAB, the cardiac patch was attached to the epicardium of the right ventricle (RV). Cardiac function was evaluated using echocardiography and catheterization for 9 weeks after PAB, comparing the patch (n = 7) and sham (n = 10) groups.ResultsNine weeks after PAB, the RV wall was thickened, the RV cavity was enlarged with a reduced left ventricular cavity, and RV wall interstitial fibrosis was increased. However, these effects were diminished in the patch group. Left ventricular ejection fraction in the patch group was higher than in the sham group (p < 0.001), right end-systolic pressure was lower (p = 0.045), and tricuspid annular plane systolic excursion improved in the patch group (p = 0.007). In addition, von Willebrand factor expression was significantly greater in the patch group (p = 0.007).ConclusionsThe placement of a degradable, biohybrid patch onto the RV in a right ventricular failure model with fixed afterload improved myocardial output, moderated pressure stress, and was associated with reduced right ventricular fibrosis.